Waist circumference and waist-hip ratio as screening tools for hypertension in children aged 6–11 years - Esti Istiqomah; Dida A. Gurnida; Dany Hilmanto; Dzulfikar Djalil Lukmanul Hakim; Prima Nanda Fauziah (Paediatrica Indonesiana, 2019)
Background Hypertension in children is associated with obesity. 7 The renin-angiotensin-aldosterone system has been associated with intra-abdominal fat tissue. Anthropometric parameters for determining nutritional status include waist circumference and waist-hip ratio. Many studies have shown that waist circumference and waist-hip ratio are more precise to determine overweight or obese.